Target marker as control point in crime scene modeling by using close range photogrammetry / Nurul Hidayah Zulkarnain - Zulkarnain, Nurul Hidayah (2019)
Crime scene is one of the most secured place which cannot be access easily and all the evidence and other things in the scene should not be touch or move which could happened in room or open area. The main objective of this paper is the use of the target marker as the control point will determine the exact x,y and z position of the evidences and victims in addition produce 3-dimensional modelling. Approximately two or more control points using target marker which the positions are justify by using handheld application which is "Easy GPS" will be located at the comer of the room by using close range photogrammetry. By using Photomodeler Scanner and Agisoft Photoscan software, the positions of the evidences and victims can be transferred from control points. At the same time, the 3-dimensional modelling can be developed and the evidences and victims can be measured. The accuracy of the measurement compared with conventional measurement by using ruler. In conclusion, this study provides a vital step in forensic mapping applications for police investigators. It provides the practical solution to mapping crime scene by using close-range photogrammetry methodology.